2016
DOI: 10.1158/0008-5472.can-15-2770
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Establishes an Immunosuppressive Microenvironment during the Early Stages of Breast Carcinogenesis to Promote Tumor Growth and Metastasis

Abstract: Immunosurveillance constitutes the first step of cancer immunoediting in which developing malignant lesions are eliminated by anti-tumorigenic immune cells. However, the mechanisms by which neoplastic cells induce an immunosuppressive state to evade the immune response are still unclear. The transcription factor Stat3 has been implicated in breast carcinogenesis and tumor immunosuppression in advanced disease, but its involvement in early disease development has not been established. Here, we genetically ablat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 43 publications
3
77
0
Order By: Relevance
“…A recent study provided the first experimental evidence that STAT3 is essential for the establishment of immunosuppression during the earliest stages of breast cancer progression34. This is consistent with our observations that mammary epithelial STAT3 loss profoundly impairs breast cancer development in immunocompetent, but not immunodeficient, mice.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study provided the first experimental evidence that STAT3 is essential for the establishment of immunosuppression during the earliest stages of breast cancer progression34. This is consistent with our observations that mammary epithelial STAT3 loss profoundly impairs breast cancer development in immunocompetent, but not immunodeficient, mice.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to modulating macrophage infiltration, our recent studies have indicated that epithelial activation Stat3 plays a critical role in maintaining an immune-suppressive tumor microenvironment. For example, mammary epithelial deletion of Stat3 in PyV mT model results in rapid immune-mediated clearance of emerging PyV mT tumors 22 . Collectively, these observations argue that the potent transforming properties of ErbB2Δ16 variant is due to its impact on the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…These M2 cells have a pro-tumor immune response by producing immunosuppressive factors (e.g., IL-10 and TGF-β) and exhibit a high level of intracellular STAT3 (16). STAT3 activation has also been associated with promoting immunosuppression (45). Activated STAT3 decreases the expression of surface molecules in microglia that are necessary for antigen presentation, such as MHC-II, CD80, and CD86, and also increases the expression of various M2-specific immunomodulatory mediators including IL-10, vascular endothelial growth factor (VEGF), and various matrix metalloproteinases (MMPs) (46, 47), promoting growth and invasion of the tumor.…”
Section: Classical (M1) or Alternative (M2) Microglia/macrophages mentioning
confidence: 99%